2021
DOI: 10.3389/fenvs.2021.755873
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Marine Surface Sediments of Daya Bay, Southern China: Spatial Distribution, Sources Apportionment, and Ecological Risk Assessment

Abstract: Daya Bay, especially in the northwestern region, which is a nature reserve with larval economic fish and shrimp populations, is no longer an unpolluted marine environment due to the recent increases in anthropogenic activities. This study collected seasonal surface sediment samples from 20 sites in northwestern Daya Bay to evaluate pollution and ecological risks and to identify possible sources and transport pathways of heavy metals (Cd, Pb, Cr, Cu, Zn, Hg, As). The results showed that all the heavy metal conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Numerous studies in the related literature reported that clay, silt, and organic matter particles are important carriers of TEs in sediments (Rubio et al, 2000;Vaalgamaa and Korhola, 2004;Selvam et al, 2012;Özkan, 2012;Dou et al, 2013;Hu et al, 2013;Xu et al, 2016;Zhao et al, 2017;Perina et al, 2018;Remeikaite-Nikienėet al, 2018;Sun et al, 2020; Values of Pearson correlation coefficient (r) highlighted in bold are different from 0 with a significance level a = 0.05. Wang et al, 2021;Zhou et al, 2022). On the one hand, the finer sediment fractions (clay and silt) have a higher specific surface area than the coarser fraction (sand), giving them more binding sites for the adsorption of TEs and organic matter (Rubio et al, 2000;Xu et al, 2016;Zhou et al, 2022).…”
Section: Element Concentrations In Surface Sediments and Potential Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in the related literature reported that clay, silt, and organic matter particles are important carriers of TEs in sediments (Rubio et al, 2000;Vaalgamaa and Korhola, 2004;Selvam et al, 2012;Özkan, 2012;Dou et al, 2013;Hu et al, 2013;Xu et al, 2016;Zhao et al, 2017;Perina et al, 2018;Remeikaite-Nikienėet al, 2018;Sun et al, 2020; Values of Pearson correlation coefficient (r) highlighted in bold are different from 0 with a significance level a = 0.05. Wang et al, 2021;Zhou et al, 2022). On the one hand, the finer sediment fractions (clay and silt) have a higher specific surface area than the coarser fraction (sand), giving them more binding sites for the adsorption of TEs and organic matter (Rubio et al, 2000;Xu et al, 2016;Zhou et al, 2022).…”
Section: Element Concentrations In Surface Sediments and Potential Co...mentioning
confidence: 99%
“…Accumulation of TEs in marine sediments depends on various factors, e.g., water depth, water physicochemical properties (pH, salinity, temperature, dissolved oxygen and organic matter content), sediment composition and texture, intensity/direction of winds, waves, and currents, fluvial, atmospheric, and other natural or anthropogenic inputs (Oros, 2019;Constantinescu et al, 2023). Multivariate analysis, especially PCA, is widely used to identify the main factors affecting the concentration of TEs in sediments and possible pollution sources/transport pathways (Martins et al, 2012;Kahal et al, 2018;Remeikaite-Nikienėet al, 2018;El-Sorogy et al, 2020;Perumal et al, 2021;Vilhena et al, 2021;Wang et al, 2021;Kubra et al, 2022;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, existing studies have also found a positive correlation between exposure to these toxic pollutants and development of abnormal endocrine, elevated cancer rates, immunity disorders, and increased risk of diabetes (Wang B. et al, 2019;Hashem et al, 2021). This is because of their enrichment, nonbiodegradability, high-persistency half-life of decades, as well as their inherent toxicity, biogeochemical recycling, and ecological risks (Vassura et al, 2011;Wang et al, 2021). Therefore, it is important to monitor these harmful compounds in the soil around MSW incinerator and estimate their health effects on nearby people.…”
Section: Introductionmentioning
confidence: 99%